Innovations in financing of agri-food value chains in China and India: Lessons and policies for inclusive financing - Chen, Kevin Z.; Joshi, Pramod Kumar; Cheng, Enjiang; Birthal, Pratap S. (Emerald Publishing Limited, 2015)
– The purpose of this paper is to synthesize lessons from the agricultural value chain models and their associated financing mechanisms in China and India as to provide policy recommendations on how best to facilitate development of efficient and inclusive value chains.– The paper builds on a review of the existing literature on agricultural value chains and their financing mechanisms, and draws lessons from it for strengthening interface between product and financial markets in order to enable smallholders capture benefits of the value addition.– From the comparative review of value chain financing mechanisms and current policy contexts the authors find dominance of internal financing of value chains (in terms of provision of inputs, technology and services) in both the countries. Value chain finance from commercial banks and other financial institutions is limited and mainly through tripartite agreements among the financing institutions, lead firms and farmers.– The lessons drawn from various value chain models and their financing mechanisms provide feedback to financial institutions and policymakers to take measures to strengthen value chain finance in smallholder agriculture.– The paper undertakes a rigorous review of the existing value chain models and their financing mechanisms in light of the most recent research on emerging innovations and development strategies, in order to glean key lessons for policy recommendations on strengthening linkages between financial and product markets.